Italy : Financial Sector Assessment Program; Detailed Assessment of Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies; Payment Systems Oversight. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper discusses a Detailed Assessment of the Observance of the IMF Code of Good Practices on Transparency in Monetary and Financial Policies for Payment Systems Oversight for Italy. The Banca d'Italia's (BI) oversight of payment systems is characterized by high levels of transparency, benefiting from clarity in the European Union-wide institutional framework, and actively contributing to its timely disclosure of policy developments and exchange of information. The BI routinely discloses the progress toward achieving its policy objectives, and engages in two-way communication with the markets.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet